1984
DOI: 10.2355/isijinternational1966.24.257
|View full text |Cite
|
Sign up to set email alerts
|

Manganese equilibrium between molten iron and MgO-saturated CaO-FetO-SiO2-MnO slags.

Abstract: SynopsisManganese distribution between liquid iron and Mg0-saturated Ca0-FetO-Si02 Mn0 slaps containing P205 or S has been obtained in the temperature range 1 550 to 1 650 °G by use of magnesia crucibles. The manganese distribution ratio was found to increase with increase in Si02 content and decrease in temperature. The good relationship between activity coefficient of Mn0 or equilibrium quotient kMn (= (%Mn0)/ { [%Mn]. (%Fet0)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 0 publications
9
65
1
Order By: Relevance
“…the molar fractions of cations multiplied by the number of oxygens in the respective component. The present work plotted together with the results obtained by Shim and Ban-ya 8) and Suito and Inoue 9) show similar tendency as shown in Fig. 7 although the steelmaking slag-related data have slightly lower MgO solubility.…”
Section: Correlation Of Mgo Solubility With Optical Basicitysupporting
confidence: 68%
See 1 more Smart Citation
“…the molar fractions of cations multiplied by the number of oxygens in the respective component. The present work plotted together with the results obtained by Shim and Ban-ya 8) and Suito and Inoue 9) show similar tendency as shown in Fig. 7 although the steelmaking slag-related data have slightly lower MgO solubility.…”
Section: Correlation Of Mgo Solubility With Optical Basicitysupporting
confidence: 68%
“…In Fig. 3 8,9) measured at 1 873 K, which can be easily explained considering that the general dissolution of solid phase into liquid slag is endothermic.…”
Section: Effect Of Slag Compositions On Mgo Solubilitymentioning
confidence: 99%
“…1-9.6) in open-hearth slags and indicated that MnO is a more basic constituent than FeO. Suito and Inoue 5) measured the manganese distribution between liquid iron and MgO-saturated CaO-SiO 2 -Fe t O-MnO slags (MnOϽ5.3 mass%) containing P 2 O 5 or S in the temperature range of 1 823-1 923 K. According to their results, the manganese distribution ratio was found to increase with an increase in SiO 2 content and decrease in temperature. Recently Morales and Fruehan 6) investigated the thermodynamics of manganese oxide and iron oxide of CaO-SiO 2 -Fe t O-MgO sat -MnO-P 2 O 5 slags with high MnO contents (MnOϽ25 mass%) relevant to the smelting of MnO ores in steelmaking.…”
Section: Introductionmentioning
confidence: 99%
“…6. The results of Suito et al 38) and Morales et al 18) for ferromanganese slags are also plotted. There is considerable scatter in those data.…”
Section: Manganese Equilibriummentioning
confidence: 99%
“…However, g MnO increases as B the increases. According to modern slag theory, the reason is attributed to the preferential association of [38][39][40] suggest that the increase continues until a maximum B-value is reached, after which the value of g MnO remains constant. In order to prevent the oxidation loss of Mn from steel, a MnO must be maximized without increasing X MnO .…”
Section: Manganese Equilibriummentioning
confidence: 99%